Design of Coordination Between Signalized Intersections (A Case Study in Gayamsari and Lamper Intersections) - Ramadan, Ramadan; Setiadji, Bagus Hario; Riyanto, Bambang (Journal La Multiapp, 2025)
Gayamsari Intersection and Lamper Intersection in Semarang City are signalized intersections that experience high levels of vehicle queues and delays, especially during peak hours. This study aims to design signal coordination between intersections to improve traffic performance. The analysis was conducted based on the Indonesian Road Capacity Guidelines (PKJI) 2023, with a five-day field survey covering active days (Monday-Wednesday) and weekends (Saturday-Sunday). Peak hour traffic volume data was used to analyze existing conditions, including degree of saturation (DJ), queue length (PA), and delay (T) parameters. Several signal cycle planning scenarios were tested, and an optimal cycle of 180 seconds for weekdays and 130 seconds for weekends was obtained. Signal coordination can only be applied from Lamper to Gayamsari intersection, because in the reverse direction straight vehicles at Gayamsari intersection do not face red signals. Signal coordination is designed using the bandwidth and offset time method, with an offset of 45 seconds. The design results show a bandwidth of 60 seconds (morning) and 81 seconds (afternoon) on active days, and 43 seconds (morning) and 51 seconds (afternoon) on weekends. This design is expected to reduce vehicle delays and queues, and improve traffic efficiency at both intersections.